Triple Positive Solutions of M-Point Boundary Value Problem on Time Scales With P-Laplacian - Dogan, A. (Iranian Mathematical Soc, 2017)
In this paper, we consider the multipoint boundary value problem for one-dimensional p-Laplacian dynamic equation on time scales. We prove the existence at least three positive solutions of the boundary value problem by using the Avery and Peterson fixed point theorem. The interesting point is that the non-linear term f involves a first-order derivative explicitly. Our results are new for the special cases of difference equations and differential equations as well as in the general time scale setting.
Keywords: Time Scales; Boundary Value Problem; P-Laplacian; Positive Solutions; Fixed Point Theorem